The Teacher’s Beliefs and Practices on the Use of Digital Comics in Teaching Writing: A qualitative case study - Muflikhatun Nisa Muyassaroh; Abdul Asib; Sri Marmanto (International Journal of Language Teaching and Education, 2019)
In the industrial era 4.0, the use of digital comic as a multimodal teaching medium is seen as the new trend in EFL classrooms. Although many teachers had already used this medium, so far, there was not any study which inquires the use of comic in another setting such as vocational high schools. Considering this gap, this study aimed to explore teacher belief, practice, and problems in implementing digital comics to teach writing for vocational students. This study used a qualitative case study approach. The subject was an experienced English teacher who held M. A. in English language. As the findings, the teacher believed that the implementation of comics-manga was the best method to switch the vocational students’ stereotype on English; from English as the most difficult subject to English as the enjoyable subject. This medium was implemented by using the genre approach. However, as the consequence, the combination of digital comics and process approach confronted a major challenge, namely time management.